Security‑related Cooperation among the V4 States - Ušiak Jaroslav (Politics in Central Europe, 2018)
The need for security and defence cooperation is a significant driver bringing together many nation‑state groupings. Today, the renewal and strengthening of this cooperation is a pressing concern for all such alliances around the world. This cooperation is rooted in the history that initially highlighted its potential, but it also encompasses contemporary relationships formed under the influence of enormous challenges and pressures. Finally it draws on the past successes and failures of the group in question. The aim of this study is to trace the beginnings of the security‑related cooperation of the Visegrad countries and locate the point of coordination of their respective security policies. My methodology is based on an analysis and synthesis of key source materials, making use of different types of analytical approaches. In order to identify the factors that connected the V4 states, I have applied a comparative method. My conclusion highlights important areas of security‑related cooperation ranging from the coordination of energy policies to military and defence matters and social protection including the fight against extremism, radicalism and hybrid threats.